Correlates of Increased Chemerin but Reduced Oxytocin with Adiposity and Atherogenecity Indices in Metabolic Syndrome Patients - Kasabri, Violet; Al-Neimat, Oneassa; Naffa, Randa; Akour, Amal; Abu Jbara, Mousa; Bustanji, Yasser (Jordan Journal of Pharmaceutical Sciences, 2019)
OBJECTIVES: the neurohypophysial hormone Oxcytocin (OXT) and an adipokine Chemerin have got a growing evidences about their roles in metabolic syndrome (MetS) and type 2 diabetes (T2DM). we aimed to compare and correlate OXT and Chemerin plasma levels with each other as well as conicity index (CI), waist circumference (WC), waist-to-hip (WHR) ratio, and body mass index (BMI), lipid profile, atherogenicity index (TG/HDL-C ratio), red cell distribution width (RDW) and mean platelet volume (MPV). METHODS: in this cross-sectional study, 30 normoglycemic lean subjects (control), 30 normoglycemic (MetS) and 29 newly diagnosed (MetS-Pre/T2DM) candidates were enrolled. Plasma Chemerin and OXT were analyzed by colorimetric-enzymatic assay. RESULTS: chemerin (ng/mL) plasma levels significantly higher in MetS and MetS-pre/T2DM groups vs. controls’ [268.05 (250.83-292.18) and 234.8 (209.25-260.6) vs. 176.7 (161.15-198.2); p< 0.001 and p=0.003, respectively]. The circulating levels of controls’OXT (pg/mL) 4176.6 (2407.13-5243.3) were significantly higher vs. MetS 1975.4 (1522.25-3191.15) or MetS-pre/T2DM 1403 (1033.95-2567.3) groups; p=0.009 and p=0.001, respectively. A higher chemerin and lower OXT levels in MetS group vs. MetS-pre/T2DM ; p= 0.002 p=0.04 respectively. MetS and MetS-pre/T2DM CI, atherogenicity index, WHR, and RDW-CV% were higher (p=0.05) vs. control group. MetS-pre/T2DM’s MPV was higher (p=0.015) vs. control group. In the total study population while chemerin directly correlated, OXT inversely correlated with each of BMI, CI, TG/HDL-C ratio, SBP, HbA1C and TG. A significant inverse chemerin-OXT relationship was observed (p=0.003, r= _0.318). COCLUSION: our study cannot rule out any potential molecular crosstalk of Chemerin and OXT in the development of MetS and T2DM